Time as sociology's basic concept: A perspective from Alfred Schutz's phenomenological sociology and Niklas Luhmann's social systems theory. (August 2019) - Tada, Mitsuhiro
This paper aims to clarify the proper position of time as sociology's basic concept in relation to meaning ( Sinn ). In sociology, the inseparable relationship between time and meaning has been clearly shown by Schutz's phenomenological sociology and Luhmann's social systems theory. Referring to the respective theories of Bergson and Husserl, Schutz argued that the problem of meaning in Weber's interpretative sociology is a problem of time. The meaning of an action that an actor subjectively thinks of is determined not by a common normative value for example, but rather through her/his own inner time: the meaning of an ongoing action ( Handeln ) is the act ( Handlung ) projected as an aim in the stream of consciousness. Similarly, Luhmann considered self-referential social systems as temporal subjects that cognize their own reality of the external world. Phenomena appearing to a social system through communicative intentionality are weighted by the system's own past and future, and are thereby selectively (not randomly) actualized as meaningful units in the present. System order (or social order) is thus temporally organized in the atemporal, chaotic world of meaning. "Self-reference" is to refer to a system's own eigen time ( Eigenzeit ), which provides the basis for a system's autonomy or freedom.